Energy Drinks and Binge Drinking Predict College Students' Sleep Quantity, Quality, and Tiredness. Issue 1 (2nd January 2018) - Patrick, Megan E.; Griffin, Jamie; Huntley, Edward D.; Maggs, Jennifer L.
Abstract : This study examines whether energy drink use and binge drinking predict sleep quantity, sleep quality, and next-day tiredness among college students. Web-based daily data on substance use and sleep were collected across four semesters in 2009 and 2010 from 667 individuals for up to 56 days each, yielding information on 25, 616 person-days. Controlling for average levels of energy drink use and binge drinking (i.e., 4+ drinks for women, 5+ drinks for men), on days when students consumed energy drinks, they reported lower sleep quantity and quality that night, and greater next-day tiredness, compared to days they did not use energy drinks. Similarly, on days when students binge drank, they reported lower sleep quantity and quality that night, and greater next-day tiredness, compared to days they did not binge drink. There was no significant interaction effect between binge drinking and energy drink use on the outcomes.